Biomechanical Effect of Margin Convergence Techniques: Quantitative Assessment of Supraspinatus Muscle Stiffness. - Taku Hatta (PLoS ONE, 2016)
Although the margin convergence (MC) technique has been recognized as an option for rotator cuff repair, little is known about the biomechanical effect on repaired rotator cuff muscle, especially after supplemented footprint repair. The purpose of this study was to assess the passive stiffness changes of the supraspinatus (SSP) muscle after MC techniques using shear wave elastography (SWE). A 30 × 40-mm U-shaped rotator cuff tear was created in 8 cadaveric shoulders. Each specimen was repaired with 6 types of MC technique (1-, 2-, 3-suture MC with/without footprint repair, in a random order) at 30° glenohumeral abduction. Passive stiffness of four anatomical regions in the SSP muscle was measured based on an established SWE method. Data were obtained from the SSP muscle at 0° abduction under 8 different conditions: intact (before making a tear), torn, and postoperative conditions with 6 techniques. MC techniques using 1-, or 2-suture combined with footprint repair showed significantly higher stiffness values than the intact condition. Passive stiffness of the SSP muscle was highest after a 1-suture MC with footprint repair for all regions when compared among all repair procedures. There was no significant difference between the intact condition and a 3-suture MC with footprint repair. MC techniques with single stitch and subsequent footprint repair may have adverse effects on muscle properties and tensile loading on repair, increasing the risk of retear of repairs. Adding more MC stitches could reverse these adverse effects.